In situ probing of the present-day zircon-bearing magma chamber at Krafla, Northeastern Iceland - Borisova, Anastassia Y.; Melnik, Oleg E.; Gaborit, Nicolas; Bindeman, Ilya N.; Traillou, Thibault; Raffarin, Marie; Stefánsson, Andri; Laurent, Oscar; Leisen, Mathieu; Llovet, Xavier; de Parseval, Philippe; Proietti, Arnaud; et al. (Frontiers in Earth Science, 2023)
Active felsic magmatism has been rarely probed in situ by drilling but one recent exception is quenched rhyolite sampled during the 2009 Iceland Deep Drilling Project (IDDP). We report finding of rare zircons of up to ~100 µm in size in rhyolite glasses from the IDDP-1 well products and the host 1724 AD Viti granophyres. The applied SHRIMP U-Th dating for both the IDDP and the Viti granophyre zircons gives zero-age (± 2 kyr), and therefore suggests that the IDDP-1 zircons have crystallized from an active magma intrusion rather than due to the 20 – 80 ka post-caldera magmatic episodes recorded by nearby domes and ridges. Ti-in-zircon geothermometer for Viti granophyre reveals zircon crystallization temperatures ~800 - 900 °C, whereas IDDP-1 rhyolite zircon cores show Ti content higher than 100 ppm, corresponding to temperatures up to ~1100 °C according to the Ti-in-zircon thermometer. According to our thermochemical model at such elevated temperatures as 1100°C, rhyolitic magma cannot be saturated with zircon and zircon crystallization is not possible. We explain this controversy by either kinetic effects or non-ideal Ti incorporation into growing zircons at low pressures that start to grow from nucleus at temperatures ~ 930 °C. High temperatures recorded by IDDP-1 zircon together with an occurrence of baddeleyite require that the rhyolite magma formed by partial melting of the host granophyre due to basaltic magma intrusion. Zr concentration profiles in glass around zircons are flat, suggesting residence in rhyolitic melt for >4 years. In our thermochemical modeling, three scenarios are considered. The host felsite rocks are intruded by: (1) a basaltic sill, (2) rhyolite magma (3) rhyolite sill connected to a deeper magmatic system. Based on the solution of the heat conduction equation accounting for the release of latent heat and effective thermal conductivity, these data confirm that the rhyolite magma could be produced by felsic crust melting as a result of injection of a basaltic or rhyolite sill during the Krafla Fires eruption (1975 AD).